Association of Employee Attributes and Exceptional Performance Rating at a National Center of the US Centers for Disease Control and Prevention, 2011. Issue 4 (July 2015) - Roberts, Henry; Myles, Ranell L.; Truman, Benedict I.; Dean, Hazel D.
Abstract : Context: Employee performance evaluation motivates and rewards exceptional individual performance that advances the achievement of organizational goals. The Centers for Disease Control and Prevention (CDC) and its operating units evaluate employee performance annually and reward exceptional performance with a cash award or quality step increase in pay. A summary performance rating (SPR) of "exceptional" indicated personal achievements in 2011 that were beyond expectations described in the employee's performance plan. Objective: To determine whether personal attributes and job setting of civil service employees were associated with an exceptional SPR in National Center for HIV/AIDS, Viral Hepatitis, STD, and TB Prevention (NCHHSTP) in 2011. Design: Data from the CDC 2011 performance management database collected in 2012 were analyzed in 2013 to identify SPR, personal attributes, and job settings of full-time civil service employees. Multivariate logistic regression controlled for confounding and stratified analysis detected effect modifiers of the association between receiving an exceptional SPR in 2011 and gender, race/ethnicity, education, job location, job series, grade level, years in grade, years of federal service, supervisory role, and NCHHSTP division. Results: Among the 1037 employees, exceptional SPR was independently associated with: female gender (adjusted odds ratio: 1.7 [1.3, 2.3]), advanced degrees (doctorate: 1.7 [1.1, 2.5] master's: [1.1, 2.0]), headquarters location (2.8 [1.9, 4.1]), higher pay grade (3.3 [2.4, 4.5]) and years in grade (0-1 years: 1.7 [1.3, 2.4]; 2-4 years: 1.5 [1.1, 2.0]), division level (Division A: 5.0 [2.5, 9.9]; Division B: 5.5 [3.5, 8.8]), and supervisory status (at a lower-pay grade) (odds ratio: 3.7 [1.1, 11.3]). Conclusions: Exceptional SPR is independently associated with personal employee attributes and job settings that are not modifiable by interventions designed to improve employee performance based on accomplishments. Abstract : This study shows that summary performance rating is independently associated with personal employee attributes and job settings.